Estudo comparado da função testicular de camundongos adultos BALB/c selvagens e portadores de mutação nos genes Foxn1 e Prkdc - Carolina Felipe Alves de Oliveira (2014)
The development of new technologies to produce mutant animals provides excelent oportunities to better understand reproductive biology. Nude and scid mice have mutations in Foxn1 e Prkdc genes. Both present an immunodeficient phenotype therefore are very atractive experimental models for several studies and experiments, including oncology and approaches involving organs and tissues transplants and grafts. Nude mice are athimic and T cells deficient, besides having lower levels of gonadotropins (LH and FSH) and testosterone. Scid mice are deficient in T and B cells and highly susceptible to infections, besides having an increase in pachytene espermatocytes apoptosis in comparison to the wild type. Altought scarce, literature available about nude and scid male mice reproductive biology indicates changes in spermatogenesis. Therefore, in the present study, we aimed to investigate the testicular function of BALB/c nude and scid in a more datailed way in comparison to the wild type using qualitative and quantitative parameters. Significant diferences were found for several parameters investigated. Thus, the lower testicular weight in nude mice determined its lower gonadosomatic index in comparison to the other strains. Following a trend already reported in the literature, nude strain presented a higher tubular diameter and, hence, a lower total tubular lenght per testis and per gram of testis. Differences in the frequency of several stages (I, II-III, V-VII, X e XII) of the seminiferous epithelium cycle were found among the three strains. However, the combination of the frequencies, taking the occurence of the meiosis as a reference, reveled that the meiotic phase was bigger in nude mice in comparison to the wild type. The Leydig cell was the testicular element whose parameters were more influenced by the immunodeficient phenotype, particularly in nude. Therefore, the numbers found for this steroidogenic cell were 92 and 122 million per gram of testis for nude and scid mice. The Sertoli cell number per testis had a positive and significative correlation with the daily sperm production per testis in the three strains investigated. On the other hand, the spermatogenic efficiency was significantly higher in scid (~44 milion of cells per gram of testis). The meiotic index showed that scid strain presents around 48% of losses along the spermatogenic process (p<0,05), followed by the wild type (43%) and nude (38%). Higher (p<0,05) relative mRNA expression for the androgen receptor was found for the immunodeficient phenotypes and the Leydig cells from this strains presented stronger imunnohistochemestry labelling in comparison to the wild type (p<0,05). In nude and scid, the 3 beta-HSD steroidogenic enzyme mRNA content was around ~50 and 25 times higher (p<0,05) in comparison to the wild type. The pixels evaluation showed that the labelling intesity for 3beta-HSD was higher in nude (p<0,05). Also the mRNA content of aromatase was higher in nude mice (p<0,05), altought the quantification did not revealed any diferences in immunolabelling intesity. Foxn1 protein was identified in the cytoplasm and nucleus of Leydig cells in wild type and scid mice, altought it was absent in nude Leydig cells nucleus. DNA-PKc presented a cytoplasmic distribution in Leydig and Sertoli cells in wild type, nude and scid. Taking together, the data obtained in the presente study demontrated that the immunodeficient nude and scid strains presented testicular features that make them important models to investigate the regulation mechanisms of the testis, particularly those involved in Sertoli and Leydig cells proliferation.